Pengaruh Model Pembelajaran Think Talk Write Terhadap Menulis Karangan Deskripsi Siswa Sekolah Dasar - khalik, Abd; sultan, muhammad asrul; Tahir, Dina (Universitas Negeri Makassar, 2022)
This research is an experimental study which is aim to find wether there is or not the effect of TTW learning model on the fift grade students' description text writing skill of SD Inpres Banga Banga, Barru Regency. The independent variable in this study is the TTW cooperative learning model, while the dependent variable is Indonesian language learning about skills of writing descriptive text. The population in this study were 112 students of SD Inpres Banga Banga, Barru Regency, while the sample was students of twenty fifth grade students. The data from this study are the results from the pretest and posttest. The data analysis technique is descriptive and inferential data analysis. The significance obtained is a value smaller than 0.05, namely 0.000 <0.05. Sig. (2-tailed) <0.05 or 0.000 <0.05 means that there is a difference from pretest (before treatment) and posttest results (after treatment) so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that the application of the TTW learning model affects the writing skills of the fifth-grade students of Inpres Banga Banga Elementary School, Barru Regency.